2011
DOI: 10.1177/0748233711409483
|View full text |Cite
|
Sign up to set email alerts
|

Blood chromium levels of children working in gem-polishing industries in India

Abstract: The gem-polishing industry in Jaipur, India employs a substantial proportion of children. The process of polishing may result in exposure to chromium in working children. Thus, this study aims to find out the levels of chromium in these working children and the associated factors. Blood samples were analysed for chromium using atomic absorption spectrophotometer. The mean blood chromium levels were 2.51 ± 1.11 mg/100 ml and 2.33 ± 1.10 mg/100 ml in working and school children, respectively, which is well withi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 8 publications
(8 reference statements)
0
6
0
Order By: Relevance
“…Among the preschool children from Guiyu, blood Cd levels exceed the reference value of 0.5 lg/L in 63% of children (Wilhelm et al 2006). Approximately, 96% of the children in the exposed group had a blood Cr [ 5 lg/L (the normal safety range of blood Cr is 1-3 lg/L) (Tiwari et al 2012). Blood Mn had the highest standard exceeding ratio of 99% ([ 15 lg/L) among the four kinds of blood heavy metals in the exposed group (the normal safety range of blood Mn is 4-15 lg/L) (Batterman et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Among the preschool children from Guiyu, blood Cd levels exceed the reference value of 0.5 lg/L in 63% of children (Wilhelm et al 2006). Approximately, 96% of the children in the exposed group had a blood Cr [ 5 lg/L (the normal safety range of blood Cr is 1-3 lg/L) (Tiwari et al 2012). Blood Mn had the highest standard exceeding ratio of 99% ([ 15 lg/L) among the four kinds of blood heavy metals in the exposed group (the normal safety range of blood Mn is 4-15 lg/L) (Batterman et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, in a high quality paper, urinary chromium concentrations were 35 times higher in working children and largely in excess of the occupational BEI for adult workers [75]. Conversely, one low quality paper reported no significant difference for blood chromium levels between gem industry workers and non-workers [16]. Numerous limitations were found for this study methodology however, including a poor sampling process, small sample size, and insufficient reporting of methods.…”
Section: Metals and Health Outcomes (N = 13)mentioning
confidence: 93%
“…Several studies stated that the working environment was below acceptable standards for ventilation, temperature, noise, water, and sanitation [16,[57][58][59]. No PPE, such as gloves, goggles, or face shields, was worn in many studies [57,60].…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies suggested that Cr(VI) is absorbed by membrane sulfate transport channel and these Cr(VI) spontaneously react to ascorbate and glutathione (intercellular reductance) and finally combined with the DNA protein complex and disrupt the normal cellular functions (Silver et al 2001;Costa 2003;Xu et al 2004Xu et al , 2005Cheunga and Gua 2007;Nickens et al 2010). Studies also suggested that Cr(VI) is responsible for the cytotoxicity, including male and female reproductive toxicity (DART IC 2008;Tiwari et al 2012;Marouani et al 2015). Saxena et al (1990) revealed that Cr(VI) is a teratogen, which can bypass the placental barrier and negatively impact the fetal development.…”
Section: Introductionmentioning
confidence: 96%